The Possibilities of Democracy in Spinoza and Hobbes (Global Journal of Human-Social Science, 2018)
Based on the works Leviathan, by Thomas Hobbes, and Political Treaty, by Baruch de Spinoza, this paper aims to study the extent to which the theme of democracy is present in the thinking of the two philosophers. To do so, a review of the political and anthropological concepts of both -such as pact and marital status, forms of government, human nature, state of nature and freedom -will be made. Then, the intention is to find, in the relation between such concepts, the ideas that will reflect in the conceptions of the two authors about democracy.